A Review of Transnational Regulations in Environmental Protection and the Circular Economy - Zofia Wysokinśka (Comparative Economic Research. Central and Eastern Europe, 2020)
The aim of the paper is to present a review of transnational regulations (global and European) in the field of environmental protection and the circular economy. The paper discusses the regulations proposed in publications and reports of such glob-al organizations and UN Agencies as the United Nations Environmental Program (UNEP), the United Nations Conference for Trade and Development (UNCTAD), the Food and Agriculture Organization (FAO), as well as the World Trade Organization (WTO), and the European Commission as the Executive Body of the European Un-ion. With regard to the WTO, these regulations concern the effects of liberalizing trade in environmental goods and services and environmentally sound technolo-gies. Sustainable development means, above all, protecting the natural environment and reducing excessive dependence on depleting natural resources, including primary raw materials, in the economic sector. This implies the need to implement a new resourceefficient development model, based on the principles of the cir-cular economy (CE), which has been proposed for several years by transnational organizations. In the CE model, the use of natural resources is minimized, and when a product reaches the end of its useful life, it is reused to create additional new value. This can bring significant economic benefits, contributing to new production methods and new innovative products, growth, and job creation.The topics mentioned above are the main subject of consideration in the presented paper.
Keywords: O13; 330; transnational and European regulations; environmental protection; circular economy; global organizations; European Union